BERPINDAH DARI MIMBAR KE MEDSOS: TANTANGAN DALAM MEMBANGUN AUDIENS DAKWAH DI MEDIA DIGITAL - Muliawan, Juan (Jurnal Dakwah Tabligh, 2023)
This research, titled "Transitioning from Pulpit to Social Media: Challenges in Building Dawah Audiences in the Digital Media," explores the shift in Dawah communication from the pulpit to social media and its associated challenges. In the digital era, preachers face new dynamics in building dawah audiences. The study aims to comprehend the main challenges preachers confront when transitioning to digital media, as well as the strategies employed to construct and sustain dawah audiences. The research methodology involves interviews and content analysis of digital media. Findings provide insights into the dynamics of the transition of dawah communication platforms and contribute to understanding dawah practices in the digital media era.